Selective Fischer–Tropsch synthesis for jet fuel production over Y3+ modified Co/H-β catalysts. Issue 7 (12th May 2020) - Yang, Meng; Zhu, Lingjun; Zhuo, Yexin; Liang, Jiacheng; Wang, Shurong
Abstract : Y 3+, exchanged with the H protons in zeolites, decreased the acid strength of Co/Y-β- x ( x = 1, 2, 3, 4) catalysts, which reduced the selectivity of gaseous hydrocarbons (C1 –C4 ) and promoted the generation of JFRHs. Abstract : Co/Y-β- x catalysts were prepared by Y 3+ multiple ion-exchange with H-β zeolites followed by wet-impregnation of cobalt. With Y promotion, the activity of CO hydrogenation and selectivity of jet fuel range hydrocarbons were improved in the selective Fischer–Tropsch reaction. This could be attributed to the reduction of the average crystallite size of Co, the increase of its active surface area, caused by the improvement of the dispersion and reducibility of Co3 O4, and the adjustment of acid sites in the catalysts. However, an excessive addition of Y 3+ led to the increase of Brønsted acidity, deriving from the hydrolysis of Y 3+ adsorbed on the surface of H-β zeolite. Therefore, the Co/Y-β-3 catalyst with an appropriate proportion of Y achieved an optimal JFRH selectivity of 41.2% with a yield of 34.5%.